Eksplorasi Kecerdasan Emosi Dan Adaptabilitas Karier Mahasiswa - Damian Mahesa Nurwandono; Miftakhul Jannah; Lusia Estu Ariningtyas (Universitas Muhammadiyah Gresik, 2025)
Background: The development of industry and technology will continue to advance rapidly, students as the next generation are required to have self-preparation in facing career challenges including the world of work in this case career adaptability is very necessary for students. Career transition in students occurs from the world of students (education) to the world of work (work), students who have mature emotional intelligence can display career adaptability as future planning. Emotional intelligence is the ability to manage and recognize the feelings of others, so emotional intelligence is needed to face future career challenges. Objective: This research was conducted with the aim of seeing the relationship between emotional intelligence and career adaptability in students. Method: Quantitative is the method used in this study which was carried out by distributing questionnaires, the sample was taken using purposive sampling techniques with certain criteria, 118 respondents were obtained at Faculty X, University Y who were doing an internship using a correlation test. Result: The r result of 0.708 means that there is a relationship between emotional intelligence and students career adaptability. Conclusion: High emotional intelligence in students increases career adaptability.